Case report: A case study on the treatment using icaritin soft capsules in combination with lenvatinib achieving impressive PR and stage reduction in unresectable locally progressive pancreatic cancer and a literature review - Liu, Xiaolong; Yang, Feimin; Jia, Dunmao; Dong, Xinyu; Zhang, Yizhuo; Wu, Zhengrong (Frontiers in Genetics, 2023)
BACKGROUND: Pancreatic cancer is one of the most deadly malignancies in the world. It is characterized by rapid progression and very poor prognosis. The 5-year survival rate of pancreatic cancer in China is only 7.2%, which is the lowest among all cancers, and the use of gemcitabine has been the clinical standard treatment for advanced pancreatic cancer since 1997. And the application with multidrug combinations is often limited by the toxicity of chemotherapy. Therefore, there is an urgent need for a more appropriate and less toxic treatment modality for pancreatic cancer. CASE PRESENTATION: The patient was a 79-year-old woman, admitted to the hospital with a diagnosis of unresectable locally advanced pancreatic cancer (T3N0M0, stage IIA), which its imaging showed overgrowth of SMV involvement and unresectable reconstruction of the posterior vein after evaluation. As the patient refused chemotherapy, lenvatinib (8 mg/time, qd) and icaritin soft capsules (3 tablets/time, bid) was recommended according to ours past experience and few clinical research cases. The tumor lesion was greatly reduced by 57.5% after the treatment, and the extent of vascular involvement also decreased. The medication mentioned above resulted in a significant down-staging of the patient's tumor. CONCLUSION: The better results was achieved through the treatment with icaritin soft capsules and lenvatinib in this case. Because of its less toxic effect on liver and kidney and bone marrow suppression, it is suitable to combine icaritin soft capsules with targeted drugs for treating intermediate and advanced malignancies, which brings hope to patients who cannot or refuse to take chemotherapy.